PATIENT’S EXPECTATION REGARDING COMPREHENSIVE EYE EXAMINATION AMONG YOUNG ADULTS IN SHAH ALAM - Supardi, Samsul; Razak, Shaz’ Ain; Rahmat, Baqiatul Sabiqi Assfi (International Journal of Allied Health Sciences, 2021)
Background: Understanding patient’s expectation is the key element in delivering a high quality eye care services. Previous expectation studies have been focused on primary care settings and special cluster, yet little is known about local young adults expectations in an eye care. Therefore, the aim of this research is to investigate the expectation regarding comprehensive eye examination among young adults in Shah Alam. Methodology: A cross-sectional study was conducted to investigate the patient’s expectation on comprehensive eye examination by using Eye Care Expectation Survey (ECES). It consists of socio-demographic question in part one and factors contributes to eye care expectation survey in part two. ECES was distributed to two groups, those who have attended and those that have not attended comprehensive eye examination in Shah Alam. Results: A total of 206 has participated in this study with mean age of 22.42 ± 2.76 years, 64 (31.1%) of the participants are males and 142 (68.9%) are females. From this study, 113 (54.9%) have attended while 93 (45.1%) have not attended comprehensive eye examination. Overall, communication and clinical competence is the highest factor (35.3%) followed by information about diagnosis and prognosis (29%), interpersonal manner (18%) and patient involvement in eye care (14.6%). Among all factors of eye care expectation, all factors show significance association between attended and non- attended eye examination (p<0.05) except on the interpersonal manner. Conclusion: In conclusion, communication and clinical competence is the important factor that patient anticipate in comprehensive eye examination. Thus, addressing the patient’s expectation will assist in adherence of treatment given. Keywords: patient’s expectation, eye examination, eye care